Bullous Ichthyosiform Erythroderma With Unusual Presentation - Ghosh Arghyaprasun; Dey Sunil Kumar; Mandal Kakali; Kundu Mousumi (Wolters Kluwer Medknow Publications, 2003)
Bullous ichthyosiform erythroderma is a rare autosomal dominant disorder of keratinization resulting in increased epidermal cell transit time. We describe a teenager who had five members of his family similarly affected with sparing of face, neck and upper part of chest.